2022
DOI: 10.3390/cells11132040
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and Its Role in Chronic Diseases

Abstract: Ferroptosis, which has been widely associated with many diseases, is an iron-dependent regulated cell death characterized by intracellular lipid peroxide accumulation. It exhibits morphological, biochemical, and genetic characteristics that are unique in comparison to other types of cell death. The course of ferroptosis can be accurately regulated by the metabolism of iron, lipids, amino acids, and various signal pathways. In this review, we summarize the basic characteristics of ferroptosis, its regulation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 228 publications
0
41
0
Order By: Relevance
“…Since ferroptosis has been associated with several diseases [9][10][11][12][13]42,43 , our findings might have implications of medical interest. Concretely, ferroptosis propagation has been proposed to play a role in the formation of necrotic tissue in intestinal epithelium 44 , heart tissue [45][46][47] , excitotoxicity in brain 48 and renal tubula 23 , which underpins the patho-physiological relevance of this cell-contact dependent process 7,23,25 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Since ferroptosis has been associated with several diseases [9][10][11][12][13]42,43 , our findings might have implications of medical interest. Concretely, ferroptosis propagation has been proposed to play a role in the formation of necrotic tissue in intestinal epithelium 44 , heart tissue [45][46][47] , excitotoxicity in brain 48 and renal tubula 23 , which underpins the patho-physiological relevance of this cell-contact dependent process 7,23,25 .…”
Section: Discussionmentioning
confidence: 87%
“…While lipid peroxides accumulation has been identified as key event during ferroptosis, the molecular mechanisms governing ferroptosis regulation and execution remain poorly understood 7,8 . Ferroptosis has been associated with a number of diseases, including neurodegeneration, kidney failure or stroke [9][10][11][12][13] . In addition, induction of ferroptosis holds potential as an anti-cancer treatment strategy for refractory cancers.…”
Section: Introductionmentioning
confidence: 99%
“…As a newly discovered form of regulated cell death, ferroptosis is morphologically, chemically, and genetically different from apoptosis, autophagy, necroptosis, and pyroptosis, and is regulated by its unique metabolism and regulatory mechanism [ 1 , 3 ]. With the increasing studies in recent years, more and more evidence demonstrated that ferroptosis may play a significant role in multiple physiological and pathological processes, such as embryonic development, cancer, neurodegeneration disease, and organ disorders caused by drug-induced toxicity or ischemia/reperfusion injury (IRI) [ 4 , 5 , 6 , 7 , 8 , 9 ]. In cancer, ferroptosis is reported to play an essential role in suppressing spontaneous tumorigenesis in mouse models [ 10 , 11 ]; many cancer cells resistant to conventional therapies were found to be susceptible to ferroptosis [ 12 , 13 ], suggesting that the induction of ferroptosis in cancer cells is a promising anti-tumor strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is characterized by iron overload, the accumulation of lethal lipid hydroperoxides, a weakened antioxidant capacity, and mitochondrial changes such as smaller mitochondria, diminished or absent mitochondrial cristae, and ruptured mitochondrial outer membranes [ 7 , 8 ]. These manifestations are distinct from those of apoptosis, necroptosis, and pyroptosis [ 9 ]. In ferroptosis, lipid peroxidation is caused by reactive oxygen species (ROS) derived from the Fenton reaction, and the accumulation of these peroxides on cellular membranes can damage the membranes and cause cell death [ 10 ].…”
Section: Introductionmentioning
confidence: 99%